Talking to learn science: examining the role of teacher talk moves around visual representations to learn science. (2nd January 2020) - Adams, Jonathon; Chin, Tan Ying; Tan, Poh Hiang
ABSTRACT: This paper was part of a larger study to examine one primary and one secondary teacher's classroom. The study analysed the classroom discourse to describe the types of interaction and illustrate how the teachers used talk moves to mediate talk for learning science around visual representations (VRs). The study employed ethnographic approaches to collect and analyse classroom data as "snapshots of practice" in two Singapore classrooms. The findings identified that both teachers featured interactive/authoritative discourse, with the primary teacher using talk moves to unpack science terms through eliciting student observations of diagrams followed by talk moves for students to make connections to the meanings represented in the associated graph. The secondary teacher featured an interactive/dialogic approach, using talk moves around student-generated VRs for students to predict, reason and revise their representations. The findings highlighted the value of examining talk from dialogic and authoritative approaches to better understand how teachers provide opportunities for students to learn science through talk around VRs.